1968
DOI: 10.1021/jf60159a003
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of extract from pyrethrum flowers (Chrysanthemum cinerariaefolium)

Abstract: The fatty acid fraction from an unrefined commercial pyrethrum extract containing 30% "pyrethrins" was isolated and the methyl esters were separated by column chromatography on silica gel into saturated or olefinic nonhydroxy acids and a hydroxy acid fraction. Combined fatty acids represented up to 40% of the pyrethrum extract, approximately 18% being nonhydroxy fatty acids. The latter were examined by gas chromatography and a series of normal saturated acids from C!4 to C30 was identified. The major acids wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Increase in heart beat in some mice was noticed during the first 20 min. According to a previous study (Rao et al, 1973;Sashida et al, 1983) flavonoid, fatty acids (Head, 1968) and essential oils (Saggar et al, 1997) were identified in Pyrethrum plant.…”
Section: Discusionmentioning
confidence: 96%
“…Increase in heart beat in some mice was noticed during the first 20 min. According to a previous study (Rao et al, 1973;Sashida et al, 1983) flavonoid, fatty acids (Head, 1968) and essential oils (Saggar et al, 1997) were identified in Pyrethrum plant.…”
Section: Discusionmentioning
confidence: 96%